Policy on Halal Slaughtering Availability for Halal Chicken Needs Makassar City Indonesia - Nusran, Muhammad; Triana, Dien; Raehana, Syarifa; Damis, Hasanudin; Syarifudin, Ahmad; Wekke, Ismail Suardi (International Journal of Engineering and Technology, 2018)
The need of broiler chickens in Makassar is showing the elevating tendency directly with population growth rate. The base problem is low number of halal broiler chickens caused by low number of halal slaughter man (JULEHA). The purpose of this research is to design the needs of JULEHA so it fulfill the need of halal broilers chickens and mapping the existence of chicken slaughterhouse in Makassar. This Research used observation method and deep interview method with analysis of simulation of system dynamics. Result showed the need of halal broiler chicken very high are 45.000 heads/day, while amount of JULEHA only 60 person from 20 halal slaughterhouse. The ability of one person of JULEHA for slaughter is 150 heads chicken/day it means 9000 heads/day, it only covers 20% of daily needs of halal broiler chicken. it means that product of 36.000 broiler chickens is doubt. In the future Makassar needs a number of JULEHA to be trained and certified. Conclusion of this research is availability of halal broiler chickens must be supported by government through trained and certified JULEHA. Government must encourage and support with the right policy for halal broiler chickens can meet the needs of consumers in Makassar.